The Effect of Traditional Management Burning on Lichen Diversity - Davies, G. Matt (Applied Vegetation Science, 2008)
Question: How does regular management burning of a northern, Calluna vulgaris-dominated heathland affect the lichen diversity at the patch and landscape scale? Location: Mar Lodge Estate, Scottish Highlands, United Kingdom. Methods: 26 fire sites of different ages and 11 long-term unburnt stands were surveyed to create a chronosequence of changing lichen diversity following burning. Data were analysed graphically, with a GLM and using a CCA. Results: Though the immediate effect of fire was to significantly reduce lichen diversity, it generally recovered within 20 years. There was a significant difference in the population dynamics between wet and dry moorland areas with terricolous lichens in the former site being replaced by pleurocarpous mosses. Older stands, unburnt for 25 years or more, generally had lower diversity than stands 10 to 15 years old. Changes in lichen diversity and community composition can be attributed to the development of Calluna stand structure following burning. Conclusions: Fire can be seen to play an important role in maintaining the diversity of lichens in heathland areas by providing a variety of stand-structures and ages across the landscape that favours the development of greater beta-diversity.